Efficiency of Recombination Reactions Catalyzed by Class 1 Integron Integrase IntI1 - Collis, Christina M. (American Society for Microbiology, 2001)
The class 1 integron integrase, IntI1, recognizes two distinct types of recombination sites, attI sites, found in integrons, and members of the 59-be family, found in gene cassettes. The efficiencies of the integrative version of the three possible reactions, i.e., between two 59-be, between attI1 and a 59-be, or between two attI1 sites, were compared. Recombination events involving two attI1 sites were significantly less efficient than the reactions in which a 59-be participated, and the attI1 × 59-be reaction was generally preferred over the 59-be × 59-be reaction. Recombination of attI1 with secondary sites was less efficient than the 59-be × secondary site reaction.